Building Self-Efficacy in Physics Learning Using Scaffolds - Abu Yazid Raisal; Rukiyati Sugiyo; Arif Sapta Mandala (Universitas Negeri Malang, 2022)
One of the students’ main obstacles in studying physics is their low self-efficacy. A person’s self-efficacy level affects their process of behavior selection, determining the amount of effort against obstacles, determining ways of thinking and emotional reactions, along with predicting future behavior. This study used a qualitative method with a descriptive approach. Teachers can use scaffolding to increase students’ self-efficacy in learning. Scaffolding is a series of activities carried out to help children learn. The teacher provides excellent assistance to students during the early stages of learning; then, the assistance is slowly reduced until students can learn independently.Keywords: self-efficacy, physics learning, scaffolding AbstrakSalah satu hambatan yang utama muncul dari dalam diri siswa ketika belajar fisika adalah self-efficacy siswa yang rendah. Tingkat self-efficacy seseorang memiliki peran dalam menentukan pemilihan perilaku, menentukan besarnya upaya terhadap hambatan, menentukan cara pikir dan reaksi emosional, dan prediksi perilaku yang akan muncul. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan deskriptif. Guru dapat menggunakan scaffolding untuk meningkatkan self-efficacy siswa pada pembelajaran. Scaffolding merupakan serangkaian kegiatan yang dilakukan untuk membantu anak dalam belajar. Guru memberikan bantuan besar kepada siswa selama tahap awal pembelajaran kemudian seiring waktu bantuan perlahan dikurangi hingga siswa mampu melakukannya secara mandiri. Kata Kunci: self-efficacy, pembelajaran fisika, scaffolding